Internationally Linked Firms, Integration Reforms and Productivity : Evidence from Pakistan - Lovo, Stefania; Varela, Gonzalo (World Bank, Washington, DC, 2020)
This paper examines productivity dynamics and drivers for Pakistani firms listed in the stock exchange (publicly listed firms) over 2012-17. It relies on policy and outcome measures of integration in upstream merchandise and services sectors, to assess their impact on productivity downstream. The paper presents three main findings. First, the productivity of publicly listed firms remained stagnant over the period, in line with macro-level indicators for Pakistan. Second, foreign-owned or exporting firms are more productive than domestic-owned or domestic-oriented firms. Foreign investors target more productive firms, and their productivity grows after being acquired. Exporters tend to exhibit productivity growth after becoming exporters. Third, increased import duties on intermediates, or reduced levels of foreign direct investment in upstream services sectors, are associated with decreases in the total factor productivity of firms downstream. Gains from lower input tariffs accrue to those that do not secure duty exemption schemes -- domestic-oriented firms or smaller exporters. Gains from upstream services foreign direct investment accrue mostly to firms that are further from the productivity frontier. Taken together, these results suggest that productivity growth in Pakistan would benefit from increased exposure of upstream sectors to global markets.